IMPLEMENTASI TEORI KEPEMIMPINAN IOWA TERHADAP KINERJA GURU DI SMA WIJAYA PUTRA - Rohmah, Azizatur; Erianti P, Nagita Dwi; Alfiatin N, Labibah; Najwa, Fitri Adelia; Putri, Aula Rahma; Mahardika Putri, Amalia Wulan; Wahyu Pamungkas, Dimas Dzakiy; Roesminingsih, Erny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Iowa Leadership Theory on teacher performance at SMA Wijaya Putra Surabaya. The research used a qualitative method with narrative and ethnographic approaches through observations and interviews with the principal and teachers. The results showed that the principal applied a democratic leadership style characterized by open communication, participatory decision-making, and a humanistic approach. Teachers were also given motivation, appreciation, and opportunities for professional development. Routine evaluations and participatory supervision had a positive impact on improving teacher performance. This study concludes that the democratic leadership style based on Iowa Leadership Theory positively influences teacher motivation and performance while creating a conducive educational environment.